Prototipe Sistem Keamanan Pintu Rumah Berbasis Single Board Computer (SBC) - Khairul Fikri; Mohammad Hafiz Hersyah; Nefy Puteri Novani (CHIPSET, 2020)
Security is very important necessary for everyone, one of that security’s needed is the savety of valuables both publicly and more especially at home. Because many of thieves who come direcly to the house, the door was forced open, ande forgot to close the door, the thefs cases increased. Therefore the system can detect movement in front of the door using a PIR sensor design, gives a warning when the door is forced open and can open or close the door automatically. This research uses the Telegram Bot to send orders and receive notifications in the form of text or images. The PIR sensor will give notification when a movement is detected in front of the door, onece detectedit will turn on the LED light and take a picture of the movement, a warning from the system in the form of buzzer. It will also serve as a warning when the door is forced open. When the user enters the open command via Telegram Bot, the door will open and close by itself. The error of the tested system is 0%, all components can work as expected.